2021
DOI: 10.1186/s13034-021-00399-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pandemic sleep behavior and adolescents’ stress during Covid-19: a prospective longitudinal study

Abstract: Objective To prospectively document changes in adolescents’ sleep before versus during the COVID-19 pandemic, and to examine their impact on adolescents’ perceived stress. Methods Sixty-two typically developing adolescents participated in the study before (Time 1: January 15 to March 13, 2020) and during (Time 2: May 15 to June 30, 2020) the COVID-19 pandemic in Canada. At Time 1, each participant’s sleep pattern was assessed in the home environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Overall, conflicting results have been reported. While some studies reported a relatively constant sleep time [ 62 ], multiple others reported an increase in overall sleep time [ 63 , 64 , 65 , 66 ], with most studies reporting a decrease in sleep quality [ 62 , 63 , 64 , 66 ].…”
Section: Epidemiology Of Sleep Deprivation During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, conflicting results have been reported. While some studies reported a relatively constant sleep time [ 62 ], multiple others reported an increase in overall sleep time [ 63 , 64 , 65 , 66 ], with most studies reporting a decrease in sleep quality [ 62 , 63 , 64 , 66 ].…”
Section: Epidemiology Of Sleep Deprivation During the Pandemicmentioning
confidence: 99%
“…As such, a decrease in individuals not obtaining the recommended hours of sleep has been highlighted (<8 h of sleep; 20% before the pandemic, 9.5% during the pandemic). As noted by the authors, the delayed school time could have benefited the physiologically delayed bed and wake times in this age group, thus significantly decreasing sleep debt and social jet lag [ 65 ]. In accordance with this point of view, delayed school start times have been shown to be an effective method for promoting sleep health [ 67 ].…”
Section: Epidemiology Of Sleep Deprivation During the Pandemicmentioning
confidence: 99%
“…For two consecutive months, which included lockdown and post-lockdown periods, students were asked to fill out daily sleep logs in which they reported their sleep onset and offset times. Up to now, to the best of our knowledge, sleep logs were used to investigate the effects of lockdowns on sleep–wake behavior in only few published studies [ 22 , 23 , 26 , 27 ]. In the first and last participants filled out sleep logs for one week before lockdown and again one week during lockdown, in the second, participants used a smartphone sleep app, and in the third participants used modified versions of sleep logs.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study by Gruber et al, (2021) compared the sleep of a cohort of 62 typically developing Canadian adolescents before and during the COVID-19 pandemic. Using home actigraphy and questionnaires, this study was compared sleep duration, quality, behaviours and social/ emotional states across these time points.…”
Section: Impacts Across the Globementioning
confidence: 99%
“…Interestingly, the level of social support given over the pandemic period did not have a relationship to sleep. In a similar way to Gruber et al, (2021), the authors recommend a focus on interventions to encourage cognitive reappraisal and humour in order to aid resilience, which may positively impact on sleep. It should be noted that this study was not carried out using adolescent sleep measures, which is a potential future direction for study.…”
Section: The Impact On Mental Healthmentioning
confidence: 99%